Severe IgA vasculitis with features of remitting seronegative symmetrical synovitis with pitting edema (RS3PE) syndrome in a 60‐year‐old male treated with plasmapheresis. Issue 2 (15th February 2022) - Mathew, Shawn; Goyal, Rohan; Gupta, Nealansh; Joks, Rauno
Abstract: Objective : To explore a possible association between systemic immunoglobulin A (IgA) vasculitis and RS3PE syndrome and to investigate specific treatment regimens for adults who present with IgA vasculitis with renal involvement. Methods : The patient was treated with plasmapheresis and fresh frozen plasma (FFP) every other day with 1g methylprednisolone daily for three days followed by oral prednisone taper. Mycophenolate mofetil twice daily and trimethoprim‐sulfamethoxazole for Pneumocystis jirovecii prophylaxis was started. In total the patient received two cycles of plasmapheresis and fresh frozen plasma. Results : The patient's renal function drastically improved with resolution of both abdominal pain and nausea. Conclusion : We illustrate a possible association between systemic IgA vasculitis and RS3PE syndrome, and this case demonstrates IgA vasculitis with renal involvement that acutely resolved with high‐dose glucocorticoids and plasmapheresis. Additionally, our specific treatment regimen can be a potential standard of care for adults who present with IgA vasculitis with renal involvement. Highlights: Possible association between systemic IgA vasculitis and RS3PE syndrome. Adults with IgA vasculitis with renal involvement need to be treated aggressively. IgA vasculitis with renal involvement acutely resolved with high‐dose glucocorticoids and plasmapheresis.